2014
DOI: 10.1371/journal.pone.0113756
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Anaemia among Children Aged between 6 Months and 14 Years in Kenya

Abstract: BackgroundAnaemia is one of the significant public health problems among children in the world. Understanding risk factors of anaemia provides more insight to the nature and types of policies that can be put up to fight anaemia. We estimated the prevalence and risk factors of anaemia in a population-based, cross-sectional survey.MethodologyBlood samples from 11,711 children aged between 6 months and 14 years were collected using a single-use, spring-loaded, sterile lancet to make a finger prick. Anaemia was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
69
7
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 26 publications
(26 reference statements)
28
69
7
6
Order By: Relevance
“…This finding is inconsistent with a study conducted in Kenya, which revealed thatanaemia was significantly higher in male than female children (p<0.001) [5].In the current study, though there was no significant association, children aged 48 to 59 months compared to those less age 6-11 months were 61% times less likely to develop anaemia as compared to the children aged 6-11 months (AOR=0.39, p=0.061). This finding is consistent with a study conducted in Haiti where children under 24 months were 2.6 times more likely to develop anaemia as compared to the older age (OR=2.6;P<0.001) [18].Another study conducted in Brazil also reported that children aged 24-35, 36-47 and 48-59 months were 0.61, 0.49 and 0.41 times less likely to develop anaemia [17].Another study conducted in North eastern Brazil also revealed that there was a significant association between children aged (6 to 23 months) and anaemia p<0.001) [8].The dietary sources of iron are very important to keep up with the rapid rate of red blood cell synthesis, since anaemia may result if thedietary sources are inadequate [8,20].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is inconsistent with a study conducted in Kenya, which revealed thatanaemia was significantly higher in male than female children (p<0.001) [5].In the current study, though there was no significant association, children aged 48 to 59 months compared to those less age 6-11 months were 61% times less likely to develop anaemia as compared to the children aged 6-11 months (AOR=0.39, p=0.061). This finding is consistent with a study conducted in Haiti where children under 24 months were 2.6 times more likely to develop anaemia as compared to the older age (OR=2.6;P<0.001) [18].Another study conducted in Brazil also reported that children aged 24-35, 36-47 and 48-59 months were 0.61, 0.49 and 0.41 times less likely to develop anaemia [17].Another study conducted in North eastern Brazil also revealed that there was a significant association between children aged (6 to 23 months) and anaemia p<0.001) [8].The dietary sources of iron are very important to keep up with the rapid rate of red blood cell synthesis, since anaemia may result if thedietary sources are inadequate [8,20].…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, children who tested negative for malaria parasitaemia were75% times less likely to develop anaemia (AOR=0.25, p<0.001). A study conducted in Kenya revealed thatthere was a significant association between malaria and anaemia and children were 4 times more likely to be prone to anaemia(p<0.001) [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anemia often causes high fetal mortality and abnormalities, premature deaths, low birth weights for infants, and retarded brain development, which affects over half of pre-school children and pregnant women in developing countries. 33,34 Although anemia screening is highly recommended for infants and pregnant women by the U.S. Preventive Services Task Force and other developing countries, the bottleneck in control of anemia falls on the accessible screening tools needed to eliminate distance barriers. 35 Clinical diagnosis of anemia by measuring blood hemoglobin (Hgb) levels in rural areas or low-income countries is facing substantial logistic challenges, due to the difficulties in maintaining frequent and costly medical visits.…”
Section: Introductionmentioning
confidence: 99%